Bioaccessibility analysis of toxic metals in consumed rice through an in vitro human digestion model – Comparison of calculated human health risk from raw, cooked and digested rice. (30th November 2019) - Sharafi, Kiomars; Nodehi, Ramin Nabizadeh; Mahvi, Amir Hossein; Pirsaheb, Meghdad; Nazmara, Shahrokh; Mahmoudi, Babak; Yunesian, Masoud
Highlights: Bioaccessible fraction of metal(oid)s in rice is different with its total amount. The bioaccessible of metal(oid)s in the gastric phase is more than the others phases. The bioaccessible value of metal(oid)s in oral and small intestinal phases is similar. It is better that the health risk assessment be done by bioaccessible value of metal(oid)s. Abstract: The health risk assessment of exposure to toxic metals through the consumption food crops is very important. The present study was aimed to investigate the bioaccessibility of toxic metals (including arsenic, lead and cadmium) in rice through an in vitro gastrointestinal digestion model, and assess health risks associated with these metals in raw, cooked and digested rice. Total and bioaccessible concentration of metals were measured by introducing the prepared samples into the inductively coupled plasma-optical emission spectroscopy. Based on the results, the bioaccessible toxic metals in gastric phase were significantly higher than that in both oral and small intestinal phases. The estimated concentrations of these metals in the raw and cooked rice are very far from the actual exposure state. Therefore, to assess the extent of health risks associated with the subjected toxic metals through the rice consumption, the actual exposure value of the metals (bioaccessible value) should be considered.